Plugs, socket-outlets and couplers for industrial purposes. Dimensional compatibility and interchangeability requirements for plugs, socket-outlets, ship connectors and ship inlets for low-voltage shore connection systems (LVSC) Part 5, (8th January 2020) - British Standards Institution,
No abstract available